2018
DOI: 10.1073/pnas.1719493115
|View full text |Cite
|
Sign up to set email alerts
|

Cooption of heat shock regulatory system for anhydrobiosis in the sleeping chironomid Polypedilum vanderplanki

Abstract: SignificanceAnhydrobiosis is an ametabolic state found in several organisms that can survive extreme desiccation. It is of practical interest because its application to other systems might allow room temperature preservation of cells, tissues, or organs in the dry state. The insect Polypedilum vanderplanki is the most complex animal that can enter anhydrobiosis. Proteins responsible for desiccation tolerance in P. vanderplanki are relatively well studied, but little is known about mechanisms underlying their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…We performed motif enrichment analysis to detect the transcription factor-binding elements enriched in the upstream regions of the genes in each module (CLOVER [25], randomization Inferred transcriptional regulatory network obtained by integration of those of trehalose pretreatment and rehydration. Each rectangular node refers to a transcription factor gene with the ID defined in the previous study [19]. Genes differentially expressed in trehalose pretreatment (yellow), in rehydration (blue), and both treatments (green) are shown.…”
Section: Integration Of Transcriptional Regulatory Network and Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed motif enrichment analysis to detect the transcription factor-binding elements enriched in the upstream regions of the genes in each module (CLOVER [25], randomization Inferred transcriptional regulatory network obtained by integration of those of trehalose pretreatment and rehydration. Each rectangular node refers to a transcription factor gene with the ID defined in the previous study [19]. Genes differentially expressed in trehalose pretreatment (yellow), in rehydration (blue), and both treatments (green) are shown.…”
Section: Integration Of Transcriptional Regulatory Network and Modulesmentioning
confidence: 99%
“…Although various genes related to desiccation tolerance have been detected and molecular mechanisms for the anhydrobiosis of P. vanderplanki have been inferred [9][10][11][12][13][14][15][16][17][18], the transcription factors and regulatory mechanisms that drive the expression of these genes have not been clarified. Mazin et al revealed that heat shock factor (HSF) has a substantial role in regulation of these genes [19]; the HSF-binding element is enriched in the enhancers of anhydrobiosisrelated genes. In Pv11 cells, HSF knock-down significantly decreases transcription of the genes for the antioxidant protein thioredoxin (TRX), a LEA protein, and trehalose-6-phosphate phosphatase, but not that of other anhydrobiosis-related genes [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaertn., Meyer and Scherb., 1802, in response to drying and in the course of the rehydration phase (O'Mahony & Oliver, ). It has been recently shown for the sleeping chironomid Polypedilum vanderplanki Hinton, 1951 that an important strategy is also the presence of a regulatory network able to activate different desiccation‐protective genes (Mazin et al ., ).…”
Section: How Does Anhydrobiosis Proceed?mentioning
confidence: 99%
“…Targeting to multiple subcellular compartments, including mitochondria, likely accounts for some of this apparent redundancy . It has been recently demonstrated that expression of LEA proteins and other selected desiccation‐induced genes are under control of the heat shock transcription activator system . Finally, the phylogenetic distribution across selected animal phyla (nematodes, rotifers, tardigrades, arthropods) is difficult to explain by traditional vertical gene transfer, and evidence is mounting for the involvement of horizontal gene transfer from bacteria and fungi .…”
Section: Protection Of Membranes and Mitochondria During Water Stressmentioning
confidence: 99%